Behavioral economics: science or exoticism? - I. N. Drogobytsky (Мир новой экономики, 2018)
While studying economics as a science and an active sphere of human activity, scientists aim to give consistency to their knowledge, ensure that they are adequate and constructive. To achieve the desired characteristics mentioned economic knowledge they draw on the achievements of other sciences, attracted by their methodology, tools and evidence of logic. In particular, to organize the synthesis of old and new economic knowledge in addition to the economic theory and its application specific discipline - management, marketing, forecasting, planning, accounting, control, analysis, finance, taxes, investments, etc. - Successfully used the scientific and methodological arsenal of mathematics, computer science, psychology, sociology, cultural studies, conflict resolution systems theory and other scientific fields. At various times one or another scientific field has a dominant position in economic science, which gives reason to assign it a specific place- names - natural, classical, neoclassical, behavioral. Currently dominated by the neo-classical (mainstream) the concept of the economy. The center is marked by the concept of economic man (homo economicus). It’s sort of a poluchelovek-polurobot, who knows everything, remembers everything and calculates, having stable “selfish” preferences, always act rationally, maximizing its own profits. Despite the fact that in real life it is not so - a reasonable man (homo sapiens) is always subject to the emotions and very often takes erroneous, irrational decisions - neoclassical economics continues to be zealous in mathematization and informatization of their decisions, completely oblivious to the fall of human trust in the them. In an effort to “humanize” too hard, the best solutions generated strictly deterministic algorithmic information systems, practitioners, economists transformed them into “digestible” options implemented management actions. The last being a broken through the prism of emotional and intuitive inner face of the world, decision- making, are always elements of subjectivity and irrationality. This behavior is inherent in human nature, and therefore subject to scrutiny, learning and improvement. Actually it is engaged and behavioral economics, the main provisions of which are considered in this article.